CEIDP '05. 2005 Annual Report Conference on Electrical Insulation and Dielectric Phenomena, 2005.
DOI: 10.1109/ceidp.2005.1560645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nano-sized MgO-filler on electrical phenomena under DC voltage application in LDPE

Abstract: A nanocomposite material, composed of nano-sized MgO-filler added to a low-density polyethylene (LDPE), was subjected to electrical property investigations under DC voltage application. The volume resistivity of LDPE, under 40-80kV/mm DC field at 90°C, increases by the power of 10 due to the addition of only a few percent of nano-filler. The amount of space charge in LDPE under high electric field is reduced and the ratio of stress enhancement by space charge becomes less due to the addition of nanosized MgO-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 2 publications
(2 reference statements)
1
21
2
Order By: Relevance
“…The thickness dependence of the thermal breakdown strength was shown, and the thermal breakdown strength for a 0.2 mm thick sample was almost twice as high as for a 20 mm sample. When the calculated results were compared with experimental data from [9] it was found that the experimental data showed higher breakdown strength than the calculated. Any transient effects of the DC ramp that was used in the experiments were not included in the calculations.…”
Section: Introductioncontrasting
confidence: 50%
“…The thickness dependence of the thermal breakdown strength was shown, and the thermal breakdown strength for a 0.2 mm thick sample was almost twice as high as for a 20 mm sample. When the calculated results were compared with experimental data from [9] it was found that the experimental data showed higher breakdown strength than the calculated. Any transient effects of the DC ramp that was used in the experiments were not included in the calculations.…”
Section: Introductioncontrasting
confidence: 50%
“…If the barrier, which is presumably Coulombic, is increased by nano-fillers through some mechanism, electron injection will be reduced so as to prolong tree incubation period and thereby enhance electric field strength for tree initiation. Some of electric field threshold data of electro-luminescence and space charge support the increase in the barrier height, as electron injection is suppressed due to nanostructuration (3) (11) . During the tree growth period, a tip of tree will be influenced by nano-fillers, because the spacing between neighboring nano-fillers is the same order of their diameter, i.e.…”
Section: Role Of Nano-fillersmentioning
confidence: 94%
“…Cross-linked polyethylene (XLPE) insulation with nano fillers is preferred for extra high voltage dc power cables, since it exhibited better dc dielectric performance than simple XLPE insulation [4]. In this regard, various dielectric properties of low density polyethylene (LDPE) with nano fillers such as MgO nano fillers have been intensively investigated as fundamental study [5] [6].…”
Section: Introductionmentioning
confidence: 99%